Sustainable management of soil organic matter - Rees, R. M. (Robert M.) (CABI Pub., 2001)
"This volume has been developed from papers presented at an international conference on Sustainable Management of Soil Organic Matter, held by the British Society of Soil Science in Edinburgh in September, 1999. It explores the results of recent research studies examining how organic matter functions in soils, factors affecting organic matter quality and quantity and how management of organic matter can be optimized in order to achieve sustainable farming practices. It is of interest to those researching and working in the areas of soil, environmental, plant and crop science."--Jacket